A periodic density functional study of the location of titanium within TS-1 - Gale, Julian (Elsevier, 2006)
The thermodynamics of the substitution of titanium within the silicalite framework to form TS-1 has been investigated using periodic density functional theory. In contrast to previous force field and ab initio cluster studies, the favoured tetrahedral sites are found to be T8 and T10 at the level of one titanium per unit cell, which accords with the best information currently available from diffraction studies. At lower concentrations, T4 and T11 are also important sites for substitution. Bond lengths for titanium to neighbouring oxygens are also found to be in good agreement with information from EXAFS. The present work suggests that the titanium distribution in TS-1 is not so greatly at variance with the thermodynamic site preferences as has been proposed on the basis of some previous theoretical studies.